(untitled) (Research, Society and Development, 2022)
Objective: Describe the effect of Dry Needling in the treatment of cervicalgias through an integrative literature review using scientific articles. Methodology: The current research is based on surveys found a total of 39 articles, between the years 2012 to 2021, written in Portuguese and English using the keywords dry needling. dry needling and cervicalgias. Found in the database: Google Academic, PubMed and Scielo. Results: a total of 39 articles were found, 09 (nine) in Google Scholar, 18 (eighteen) in Pubmed and 12 (twelve) in Scielo.After reading the titles, abstracts and complete articles were excluded 35 for addressing topics irrelevant to the search, or not meeting the inclusion criteria established for this integrative review. In the end, a total of 04 articles meet the criteria established for this integrative review. Conclusion: It was observed through the analyzed studies that the objectives of this article were achieved, since most of the authors concluded that the use of dry needling in the treatment of cervicalgia has been of great relevance with regard to pain reduction.